Signal transduction networks in rheumatoid arthritis - Hammaker, D (2003)
Signal transduction pathways regulate cellular responses to stress and play a critical role in inflammation. The complexity and specificity of signalling mechanisms represent major hurdles for developing effective, safe therapeutic interventions that target specific molecules. One approach is to dissect the pathways methodically to determine their hierarchy in various cell types and diseases. This approach contributed to the identification and prioritisation of specific kinases that regulate NF-κB and the mitogen activated protein (MAP) kinase cascade as especially attractive targets. Although significant issues remain with regard to the discovery of truly selective kinase inhibitors, the risks that accompany inhibition of fundamental signal transduction mechanisms can potentially be decreased by careful dissection of the pathways and rational target selection.